Correction: Developments in conducting polymer fibres: from established spinning methods toward advanced applications. Issue 110 (14th November 2016) - Mirabedini, Azadeh; Foroughi, Javad; Farajikhah, Syamak; Wallace, Gordon G.
Abstract : Correction for 'Developments in conducting polymer fibres: from established spinning methods toward advanced applications' by Azadeh Mirabedini et al., RSC Adv., 2016, 6, 44687–44716.